2021
DOI: 10.3390/ph14070645
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Computational Pharmaceutics Approaches in the Modeling and Prediction of Drug Payload in Lipid and Polymeric Nanocarriers

Abstract: This review describes different trials to model and predict drug payload in lipid and polymeric nanocarriers. It traces the evolution of the field from the earliest attempts when numerous solubility and Flory-Huggins models were applied, to the emergence of molecular dynamic simulations and docking studies, until the exciting practically successful era of artificial intelligence and machine learning. Going through matching and poorly matching studies with the wet lab-dry lab results, many key aspects were revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Higher negative docking score would enhance solubility, dissolution, and stability of the compound in carrier medium for its circulation. 24,25 The compound was also found to be interacting with the hydrophobic core (Figure 1) of the carrier, suggesting that Miglyol is superior to other biocompatible carriers for potential GMFBI.1 delivery. Moreover, the ESP map revealed GMFBI.1's amphipathic nature as it interacts with polar components and hydrophobic molecules with its hydrophobic indazole core.…”
Section: ■ Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Higher negative docking score would enhance solubility, dissolution, and stability of the compound in carrier medium for its circulation. 24,25 The compound was also found to be interacting with the hydrophobic core (Figure 1) of the carrier, suggesting that Miglyol is superior to other biocompatible carriers for potential GMFBI.1 delivery. Moreover, the ESP map revealed GMFBI.1's amphipathic nature as it interacts with polar components and hydrophobic molecules with its hydrophobic indazole core.…”
Section: ■ Discussionmentioning
confidence: 98%
“…In silico molecular docking, ESP, and MD simulation studies on GMFBI.1 in complex with Miglyol revealed that with repeated extension of this biocompatible carrier having nine units, Miglyol showed higher binding affinity for our compound with a maximum docking score of 5.3 kcal/mol (Table S1). Higher negative docking score would enhance solubility, dissolution, and stability of the compound in carrier medium for its circulation. , The compound was also found to be interacting with the hydrophobic core (Figure ) of the carrier, suggesting that Miglyol is superior to other biocompatible carriers for potential GMFBI.1 delivery. Moreover, the ESP map revealed GMFBI.1’s amphipathic nature as it interacts with polar components and hydrophobic molecules with its hydrophobic indazole core.…”
Section: Discussionmentioning
confidence: 99%
“…162,163 Despite the ability to stimulate the structure of molecules precisely, dynamic simulation is time-consuming and too expensive to be used in large databases. 164,165 AI and ML generally have been utilized in various fields of medicine, such as medical imaging and nanomedicine. 31 Integrating nanotechnology and AI leads to more innovative technologies 174,175 and gives a chance for targeted delivery to specific cells and even personalized medicine.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…It utilizes a complex and large number of data sets and accurately makes predictions without needing biological tests. The use of AI in nanoparticles was preliminary and based on molecular dynamic simulation to estimate nanoparticle-cell membrane interaction. , Despite the ability to stimulate the structure of molecules precisely, dynamic simulation is time-consuming and too expensive to be used in large databases. , Table summarizes most AI technologies that are used in the field of nanomaterials.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…The noninvasive and fast sample scan in microplate formats enables HTS with minimal off-line sample processing. It may also very well present an opportunity to combine the high-content spectral data with modeling and machine learning, which have been emerging to shorten the development cycle of pharmaceutical formulations in recent years. Among different modeling approaches, locally weighted regression (LWR) has been chosen here as an adaptive method that selects calibration samples with similar features as a query sample and builds prediction models tailored for the query sample. , For high-dimensional data, principal component analysis (PCA) helps simplify the complexity while still retaining the data trends . Both LWR and PCA have been investigated to process spectroscopic data and predict attributes of pharmaceutical formulations. …”
mentioning
confidence: 99%